Idea for creating of dream TV - the missing university-students television - Draganov, Ivan (Yearbook Telecommunications, 2016)
Abstract: Purpose: One of the problems, which lies ahead of Bulgaria is how the audience from different social groups can learn more about students and scientists. Results: Despite the large number of TV channels and stations, there are still free program niches. Contributions: Such empty niche is the idea of youth TV channel, created by students, graduates and professors. With the programs of this channel, the academic community could take active participation in the public debate about the development of the country and the society.